Strengthening Village Governance Through Whistleblowing and Local Culture for Sustainable Development Goal 16 - Gde Herry Sugiarto Asana; Komang Krishna Yogantara; Ni Ketut Rasmini (Penerbit Goodwood, 2026)
Purpose: This study aims to examine the role of whistleblowing in strengthening village governance by analyzing the relationship between whistleblowing intention and behavior, as well as the moderating role of local culture. Methodology: This study employs a quantitative approach using survey methods. The research was conducted in village governments across Bali, involving 245 respondents selected through proportional stratified random sampling. Data were collected using structured questionnaires and analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS 3.2.9. Results: The findings show that whistleblowing intention significantly influences whistleblowing behavior. Local culture positively affects both intention and behavior and significantly strengthens the relationship between whistleblowing intention and behavior. These findings indicate that cultural values play an important role in transforming ethical intention into actual reporting behavior. Conclusions: This study concludes that the effectiveness of whistleblowing systems depends not only on individual intention but also on the cultural context that supports ethical actions. Strong local cultural values encourage individuals to translate ethical intentions into actual behavior. Limitations: This study focuses only on village governments in Bali and includes limited variables. Contributions: This study extends the theory of planned behavior by integrating local culture as a contextual and moderating factor, while providing practical insights for strengthening transparency and accountability in achieving Sustainable Development Goal (SDG) 16.